The Implementation of Dharuriyat Concept by Muslims Traders in The Pemangkat Market of Sambas Regency. - Arifin, Zarul (al-'adalah, 2021)
This study aims to determine the application of the Dharûriyâ concept among Muslim food traders at Pemangkat Market, Kambas Regency. This research is qualitative descriptive using a socio-religious approach. Data were obtained through observations and interviews with shop owners/grocers of Muslims at the locations which were then analyzed using inductive analysis techniques. This study concludes that the majority of Muslim traders in Pemangkat Market have applied five aspects of the Dharûriyât concept, namely: (i) Hifz al-Din (maintaining religion), which is marked by their obedience in carrying out worship, (ii) Hifz an-Nafs (maintaining the soul), their patience to avoid conflicts between fellow traders, (iii) Hifz al-Aql (maintaining reason), which is characterized by the tendency of traders not to consume/sell liquor; (iv) Hifz al-Mal (maintaining wealth), which is indicated by a penchant for saving/investing and spending their wealth in the way of goodness; (v) and Hifz an-Nasl (maintaining offspring) which is shown by the enthusiasm of the actors to provide good education to children and feed them from lawful assets.